Anti-Inflammatory Effects of Melandrii Herba Ethanol Extract via Inhibition of NF-κB and MAPK Signaling Pathways and Induction of HO-1 in RAW 264.7 Cells and Mouse Primary Macrophages - Jeong, Yun Hee (Molecules, 2016)
Melandrii Herba (MH) is a traditional Asian medicinal herb used to treat breast cancer, anuria, and diseases of lactation. However, its biological properties and molecular mechanisms have not been fully elucidated. The purpose of this study was to investigate the anti-inflammatory activity and underlying molecular mechanism of MH ethanol extract (MHE) on the lipopolysaccharide (LPS)-mediated inflammatory response in macrophages. MHE cytotoxicity was determined using a cell counting kit (CCK) assay. The effects of MHE on the production of NO, inflammatory cytokines, and related proteins and mRNAs were determined using the Griess test, ELISA, Western blotting, and real-time RT-PCR, respectively. In addition, intracellular signaling pathways, such as NF-κB, MAPK, and HO-1, were analyzed using Western blotting. Our results revealed that MHE treatment significantly inhibited the secretion of NO and inflammatory cytokines, including TNF-α, IL-6, and IL-1β in macrophages, at sub-cytotoxic concentrations. Furthermore, MHE treatment inhibited iNOS expression and induced HO-1 expression. Finally, the transcriptional activities of NF-κB and MAPK activation were significantly suppressed by MHE in LPS-stimulated macrophages. The results indicate that MHE exerts anti-inflammatory effects by suppressing inflammatory mediator production via NF-κB and MAPK signaling pathways inhibition and induction of HO-1 expression in macrophages. Therefore, our results suggest the potential value of MHE as an inflammatory therapeutic agent developed from a natural substance.